Chip removal characteristics with constant chip cross-sectional area and different ap/fz ratios in face milling - Sztankovics, István; Kundrák, János (НТУ "ХПІ", 2017)
A main development direction in production engineering is the of the enhancement productivity of machining procedures among the increasing of the accuracy and the improvement of surface quality. Since the sizes of blanks are getting closer to the final prescribed dimensions of the parts, the depth of cut and/or the number of passes decreases. Therefore, the improved productivity in face milling can be achieved by the increase of the cutting speed and/or the feed rate values. Due to the spread use of high speed milling procedures the possibilities in the cutting speed increase are more or less applied, so the study of feed rate intensification came into view.
Keywords: cutting speed; material removal rate; cutting tool; cutting force components; finite element